Pore-Water Pressure Model for Carbonate Fault Materials Based on Cyclic Triaxial Tests - Zhu, Ling; Yang, Qingwen; Luo, Luguang; Cui, Shenghua (Frontiers in Earth Science, 2022)
Pore-water pressure generation in the saturated carbonate fault zone plays a key role in the initiation of the Daguangbao landslide, which is the largest landslide triggered by the 2008 Wenchuan earthquake in China. This paper examines the pore-water pressure behavior and the influence of cyclic stress and initial stress state, and establishes a pore-water pressure model of carbonate fault materials. A series of cyclic triaxial tests of saturated carbonate fault materials were carried out, covering a broad range of frequencies, cyclic shear stress ratios and confining pressures. The test results show that the pore-water pressure in the materials increases rapidly under cyclic loading, revealing a significant liquefaction potential. The generation of pore-water pressure is barely affected by frequency. The higher cyclic shear stress ratio accelerates the generation of the pore-water pressure, while the higher confining pressure increases liquefaction resistance. Furthermore, an energy method is proposed to evaluate the development behavior of the pore-water pressure. An energy-based pore-water pressure model that accounts for the effects of frequency, cyclic shear stress ratio and confining pressure is established. The generation of the pore-water pressure is attributed to the grain crushing in the special fault materials with low-strength calcareous cementation. This work provides a novel model and some innovative observations for better understanding the pore-water pressure behavior of carbonate fault materials under seismic loading.